A prospective single‐institution study of intraoperative radiotherapy (IORT) for early‐stage breast cancer. Issue 3 (3rd December 2020) - Nguyen, My‐Lien; Pius, Patricia; Dooley, William; Squires, Ronald; Algan, Ozer; Chen, Yong; Johnson, Daniel; Henson, Christina
Abstract: Intraoperative radiation therapy (IORT) is an option for breast‐conserving therapy in early‐stage breast cancer. IORT is given in one fraction at the time of surgery and eliminates the need for adjuvant external beam radiation therapy. However, previous trials indicate increased local failure rates compared with whole‐breast irradiation, which engenders controversy around the appropriate use of IORT. We conducted a prospective study of patients diagnosed with early‐stage breast cancer (T1‐T2, N0‐N1) at the University of Oklahoma Health Sciences Center (OUHSC) between 2013 and 2017 and treated with lumpectomy followed by intraoperative radiation therapy (IORT). Data collected included stage of disease, tumor location, histology, tumor markers, lymph node status, surgical margin size, recurrence, cosmetic outcomes, and length of follow‐up. In‐breast tumor recurrence rate (IBTR) in the 77 evaluable patients was 3.9% (3 patients). Margins were close (1 mm or less) in all three recurrent patients, and two were initially diagnosed with DCIS. Recurrence rates in our patients were comparable to prior reports. All recurrences were in patients with close margins indicating that this may represent a predictive feature for exclusion from IORT; additional studies are essential to determine the recurrence rates among patients treated with IORT and to identify potential predictors of IORT eligibility.